High-fructose and high-fat feeding correspondingly lead to the development of lysoPC-associated apoptotic cardiomyopathy and adrenergic signaling-related cardiac hypertrophy. (15th July 2016) - Huang, Jiung-Pang; Cheng, Mei-Ling; Wang, Chao-Hung; Shiao, Ming-Shi; Chen, Jan-Kan; Hung, Li-Man
Abstract: Background: The heart is a highly adaptive organ that demonstrates remarkable structural, functional, and metabolic remodeling in response to physiological and pathological stimuli. We hypothesize that the heart undergoes differential adaptations in high-fat and high-fructose diet, resulting in a distinct phenotype. Methods: High-fat and high-fructose diet-induced obese and non-obese insulin resistance (IR) rat models were used to understand how the heart adapts to long-term (12-week) overnutrition. Results: Rats fed the high-fat diet developed obese IR, whereas high-fructose diet developed non-obese IR. Obese IR rats developed fibrotic hypertrophy with impairment of preload-independent contractility. The sympathetic and renin–angiotensin–aldosterone (RAA) systems and myocardial adrenergic signaling were activated in obese IR rats. Non-obese IR rats developed apoptotic cardiomyopathy with severe systolic dysfunction. Myocardial calcium cycling regulatory proteins (CCRPs) were dysregulated in non-obese IR rats; specifically, troponin I protein expression was downregulated. Moreover, compared with the controls, lipidomics analysis revealed substantial differences in lipid metabolites in non-obese IR and obese IR rats. The overproduction of lysophosphatidylcholine (lysoPC) and fatty acids was observed in non-obese IR rat hearts. A strong correlation was observed between the myocardial lysoPC and plasma troponin I levels. Treatment of cardiomyocytes with lysoPC resulted in cell death in a dose- and time-dependent manner. The overproduction of myocardial lysoPCs was associated with circulating sPLA2 levels. Conclusion: Obese IR rats developed severe fibrotic hypertrophy with the activation of adrenergic signaling and sympathetic and RAA systems. The sPLA2 –lysoPC may play a crucial role in the induction of apoptotic cardiomyopathy in high fructose-induced non-obese IR rats.